Huston Smith Replies to Barbour, Goodenough, and Peterson - Smith, Huston 1919-2016 (2001)
Responses and clarifications are given to the three respondents to my recent book, Why Religion Matters, in which I discuss what I see as the drawbacks and inconsistencies of Darwinism. While certain of their criticisms are understandable, others are based on a misreading of my work. Finally, my critics fail to show that my book is mistaken in its central claim that the modern loss of faith in transcendence, basic to the traditional/religious worldview, is unwarranted, because science has not been able to disprove the metaphysical claim that transcendence exists.
Keywords: Transcendence; Scientism; Reductionism; Gregory Peterson; Naturalism; intelligentdesign; Ursula Goodenough; evolutionary theory; Darwinism; Ian Barbour